Infant feeding and child health and survival in Derbyshire in the early twentieth century. (January 2017) - Reid, Alice
Abstract: This paper uses detailed records relating to feeding and health for a large sample of infants born in Derbyshire in the early twentieth century to provide a more detailed and nuanced picture than has previously been possible of the extent and duration of breast-feeding, reasons for ceasing to feed and the dangers of feeding in the early twentieth century. Results indicate that breast-feeding was the norm among working class British women in the early twentieth century, but the social gradient was the inverse to that found in Britain today. However this disguises much individual variation and early weaning was more common among twins, illegitimate infants, first births, and women in poor health, which placed infants at greater risk of death from many causes of death, but particularly gastro-intestinal infections. There is evidence that health visitors were successful both in promoting breast-feeding and in supporting safe hand-feeding.